2021
DOI: 10.1016/s2666-7568(21)00093-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of SARS-CoV-2 infection according to baseline antibody status in staff and residents of 100 long-term care facilities (VIVALDI): a prospective cohort study

Abstract: Background SARS-CoV-2 infection represents a major challenge for long-term care facilities (LTCFs) and many residents and staff are seropositive following persistent outbreaks. We aimed to investigate the association between the SARS-CoV-2 antibody status at baseline and subsequent infection in this population. MethodsWe did a prospective cohort study of SARS-CoV-2 infection in staff (aged <65 years) and residents (aged >65 years) at 100 LTCFs in England between Oct 1, 2020, and Feb 1, 2021. Blood samples were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
4
69
1
Order By: Relevance
“…It is likely that duration of follow-up was shorter because regular PCR testing, which enabled estimation of most seroconversion dates for individuals included in the sensitivity analysis (108 [93%] of 116 individuals), only became widely available from June, 2020, when whole care home testing was introduced. 21 It was not possible to ascertain how many discrete infection episodes participants experienced; however, as protection against reinfection has been described for up to 10 months in this population, 10 recurrent infections were probably relatively rare. If reinfections did occur, then the rate of seroreversion might have been slightly higher than we have reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that duration of follow-up was shorter because regular PCR testing, which enabled estimation of most seroconversion dates for individuals included in the sensitivity analysis (108 [93%] of 116 individuals), only became widely available from June, 2020, when whole care home testing was introduced. 21 It was not possible to ascertain how many discrete infection episodes participants experienced; however, as protection against reinfection has been described for up to 10 months in this population, 10 recurrent infections were probably relatively rare. If reinfections did occur, then the rate of seroreversion might have been slightly higher than we have reported.…”
Section: Discussionmentioning
confidence: 99%
“… 4 There is also growing evidence that previously infected individuals develop greater antibody responses to SARS-CoV-2 vaccination than people who have not been infected. 5 , 6 , 7 Robust antibody production has been shown in older LTCF residents who have survived SARS-CoV-2 infection; 8 , 9 , 10 however, there have been few large-scale sero-surveys to describe the extent of past exposure and immunity in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Although our data do not allow a meaningful calculation of the half-life due to a cross-sectional design instead of longitudinal for each patient, the finding is in accordance with reports from others (14)(15)(16)(17), who calculated the half-life of neutralizing IgG antibodies with 140 to 220 days. Recently, colleagues reported that IgG antibodies to nucleocapsid protein reduced the risk of reinfection for up to 10 months after primary infection (18). Researchers from the University of Padua and Imperial College London tested more than 85% of the 3,000 residents of Vo' , Italy, in February/March 2020 for infection with SARS-CoV-2 and tested them again in May and November 2020.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The strong immune response after a natural infection with SARS-COV-2 is also supported by the low incidence of breakthrough infections among seropositive compared to seronegative individuals across various age groups. 23 , 24 For example, in large cohort in England (n=2,111), seropositive individuals tested at least monthly were 41-85% less likely to have a positive PCR test for SARS-COV-2 when compared to seronegative individuals. 24 Thus, the immune response induced by natural infection with SARS-COV-2 should augment the COVID-19 vaccine efforts to attain herd immunity assuming that new SARS-COV-2 variants retain significant overlap in epitopes with currently circulating variants.…”
Section: Discussionmentioning
confidence: 99%